KAJIAN MODEL PROBABILISTIK BAHAYA ABU VULKANIK PAPANDAYAN - HERIWASESO, ANJAR
Volcanic ash is one of volcanic eruption product that affecting social and economic aspect. Global impact of the volcanic ash is climatic disturbance due to its high eruption columns and its wide dispersal. Volcanic ash is abrasive and corrosive, also has several impacts on society such as disruption to the quality of soil and water supply, human health, disruption to electricity and communication systems, disruption to infrastructure and buildings, crop failure, famine, and even to cause death. Other impacts are disruption to transportation, especially aviation, both domestic and international.